Enhanced Iron Molten Air Battery Cycle Life and the Chemistry of the Nickel Oxide/Air Interface. Issue 2 (1st January 2018) - Cui, Baochen; Zhang, Jianing; Liu, Shuzhi; Xin, Hongyu; Liu, Xianjun; Lefler, Matthew; Licht, Stuart
Abstract : Iron molten air batteries are a promising technology for clean and efficient electrical power generation, but their durability is a key challenge to commercialization. Here, we replaced LiCl in the KCl-LiCl-LiOH system with Li2 SO4 or Li0.87 Na0.63 K0.50 CO3 to investigate electrode corrosion and improve cycle life. The nickel air electrode exhibited low corrosion rate in KCl-Li2 SO4 -LiOH, but the kinetics of the air electrode reactions was impaired. Electrolyte composition influences pitting corrosion of the Ni air electrode in KCl-LiCl-LiOH and intercrystalline corrosion in KCl-Li2 SO4 -LiOH. KCl-LiNaKCO3 -LiOH is a superior electrolyte for these iron air batteries with nickel air electrode. A tenacious, compact Li nickel oxide nano-scale particle layer on the nickel air surface in KCl-LiNaKCO3 -LiOH retards nickel fin matrix (current collector) corrosion allowing long-term use. The air electrode surface is an electrocatalytic layer of uniform nano-particles. The iron molten air battery cycled for 850 cycles with an average coulombic efficiency of 88.6% and average discharge potential of ∼1.04 V, achieving a ten-fold increase in cycle life in contrast with the previous result using KCl-LiCl-LiOH. This study explores key factors improving the Ni air electrode and cycle life without interfering with the cycling performance of the iron molten air battery.